2009
DOI: 10.1213/ane.0b013e31818cdb29
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neonatal Isoflurane Exposure in Mice on Brain Cell Viability, Adult Behavior, Learning, and Memory

Abstract: Prolonged isoflurane exposure in neonatal mice led to increased immediate brain cell degeneration, however, no significant reductions in adult neuronal density or deficits in spontaneous locomotion, spatial learning, or memory function were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
166
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(183 citation statements)
references
References 45 publications
12
166
2
Order By: Relevance
“…In addition, the mice showed normal food intake behavior and normal locomotive activity. The dose of midazolam (0.83 mg/kg) used in this study was low compared with other studies that used higher concentrations of benzodiazepines such as midazolam for different experimental procedures related to neuronal toxicity and apoptosis, anesthesia, and other applications (Bittigau et al, 2002;Ikonomidou et al, 2000;Jevtovic-Todorovic et al, 2003;Loepke et al, 2009;Young et al, 2005). These results indicate promising implication of midazolam, apart from anesthesia, to enhance anticancer efficacy when applied in combination with other anticancer agents.…”
Section: Midazolam Suppressed Tumor Growth In Human Tumor Xenograft Micementioning
confidence: 82%
“…In addition, the mice showed normal food intake behavior and normal locomotive activity. The dose of midazolam (0.83 mg/kg) used in this study was low compared with other studies that used higher concentrations of benzodiazepines such as midazolam for different experimental procedures related to neuronal toxicity and apoptosis, anesthesia, and other applications (Bittigau et al, 2002;Ikonomidou et al, 2000;Jevtovic-Todorovic et al, 2003;Loepke et al, 2009;Young et al, 2005). These results indicate promising implication of midazolam, apart from anesthesia, to enhance anticancer efficacy when applied in combination with other anticancer agents.…”
Section: Midazolam Suppressed Tumor Growth In Human Tumor Xenograft Micementioning
confidence: 82%
“…In initial attempts at P1-P4, before local anesthesia was introduced into the protocol, it was difficult to obtain a deep and prolonged sedation due to a narrow dose-effect window between insufficient sedation and overdose. In addition, concerns related to a neurotoxic effect of isoflurane in newborn animals have been raised [27][28][29][30] . A combination of isoflurane and the local anesthetic Bupivacaine results in a deeper and more stable anesthesia while permitting an isoflurane dose reduction by a factor of 2-3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the developing brain is susceptible to anesthetic-induced neuronal apoptosis at the peak of synaptogenesis, and the greatest vulnerability in rodents occurs predominantly from postnatal day (P) 7 to P10 (Yon et al, 2005;Rizzi et al, 2010), it was considered that anesthetic-induced acute neuronal apoptosis may be a critical contributing factor to long-term cognitive and behavioral impairment, but recent studies have demonstrated that anesthetic-induced acute neuronal apoptosis does not cause long-term cognitive impairment (Yang et al, 2014;Loepke et al, 2009). Therefore, the role of neu-ronal apoptosis in long-term cognitive impairment needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%